Perancangan Pengendali Gerakan Stepper Motor menggunakan Mikrokontroler STM32 dengan Tampilan Grafis TouchGFX - Mada Jimmy Arifianto; Heru Suprapto (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2023)
Stepper Motor is an actuator, which is often used in electromechanical systems of automation equipment or machines that require precision movement. Physical quantities in motion control are position, velocity and acceleration. To facilitate the control and monitoring of these quantities, a graphical display interface with a touch screen is proposed. In this paper, a motion controller design that integrates the STM32H743 microcontroller, TMC5160 and a 7 inch LCD touch screen will be presented. The supporting software for this system is TouchGFX as a Graphical User Interface on a touch screen. In addition, FreeRTOS is used as a microcontroller operating system to support the concept of multi-tasking in motion control applications. Hopefully, this controller design can be run without the need additional controller devices or computers. The experiment results show that the motor can be driven simultaneously on a task, while the microcontroller can perform display control with 30fps, touch screen and data communication which are handled by the scheduler in real time. The application requires 16.26% RAM and 24.14% flash of total capacity.